Människan och platsen. Några anmärkningar om Katarina Frostensons författarskap - Niewiarowska-Rasmussen, Ewa (Folia Scandinavica Posnaniensia, 2009)
Attitude towards space in a literary work is one of the two central and very problematic themes in Katarina Frostenson’s creative activity. The author introduces and describes the place in different manners and usually treats it as a living organism that one can engage in dialogue with; one that evokes memories and releases emotions. For Frostenson the place has an identity because it is the mirror of the soul. Only in contact with the place words are born and the real, inner voice of the lyric subject is released.